Application of principles of cognitive psychology in teaching: Perspectives from undergraduate medical and dental students. - Ambreen Surti; Shaur Sarfaraz; Rabiya Ali; Mukhtiar Baig; Rehana Rehman (PLoS ONE)
Introduction Principles of cognitive psychology (CP) aim to shed light on the fundamentals of perception, attention, and knowledge extraction used for critical thinking, learning, and recollection of information. These principles were incorporated to educate undergraduate medical and dental students, and the study aims to assess the perspectives of medical and dental students regarding applying these principles. Methods The descriptive cross-sectional study was carried out among 555 Bachelor of Dental Surgery (BDS) and Bachelor of Medicine, Bachelor of Surgery (MBBS) students using a validated questionnaire with purposive sampling. Data was analyzed on SPSS version 21. Results The study population comprised 555 undergraduate medical and dental students, with a mean age of 20.55 ± 1.86 years. Of these, 63.4% were pursuing MBBS, and 36.6% were BDS students. The sample included 320 (57.65%) female and 235 (42.35%) male students. MBBS and BDS students exhibited high confidence levels in most aspects of CP principles required for interactive learning. However, they expressed lower confidence in facilitator-student interaction, receiving feedback within large classes, and experiencing online teaching elements. A significant difference was observed between the two groups. In five of six CP attributes, MBBS students demonstrated significantly higher perceptions than BDS students: overcoming cognitive and emotional challenges, recognizing and overcoming ineffective learning strategies, paying attention in class, and integrating knowledge (p < 0.05). Conclusion The current study reveals that MBBS students perceived the application of CP principles more positively than BDS students in key interactive learning areas. Furthermore, the integration of CP principles enhanced session interactivity, student engagement, attention, and retention. To optimize learning outcomes, institutions should consider adopting blended learning strategies, curricular innovations, and active learning methodologies (such as case-based, team-based, and problem-solving approaches) aligned with CP principles. Future longitudinal research could provide deeper insights into the long-term impact of CP principles on student learning and perception.